(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Since the turn of the millennium, some firms havereverted to a simpler strategic structure driven by advances in informationtechnology. It is felt that knowledge management systems should beused to share information and create common goals. Strategic divisions arethought to hamper this process. This notion of strategy has been captured underthe rubric of dynamic strategy,popularized by Carpenter and Sanders’s textbook. This work builds on that ofBrown and Eisenhart as well as Christensen and portrays firm strategy, bothbusiness and corporate, as necessarily embracing ongoing strategic change, andthe seamless integration of strategy formulation and implementation. Suchchange and implementation are usually built into the strategy through thestaging and pacing facets.